The relationship between alexithymia and general symptoms of pregnant women - Gilanifar Monavar; Delavar Moloud Aghajani (Sciendo, 2017)
Introduction. Alexithymia is related to poor emotion regulation strategies as well as higher rates of somatic disorders. The aim of the present study was to assess the relationship between alexithymia and the general symptoms experienced by the pregnant women.